Exploring the Photophysical and Photochemical Properties of N -(thioalkyl)-saccharins as an Alternative Route to the Synthesis of Tricyclic Sultams - Castro Godoy, Willber David (2016)
Photocyclization of N-(thioalkyl)-saccharin was carried out to obtain different polycyclic sultams in good yields. These photoreactions were efficient under inert atmosphere and acetone triplet-sensitized conditions indicating that the triplet excited state is directly involved in the formation of annulated products. The presence of molecular oxygen changes product distribution, and only photo-oxygenation products (sulfoxides and sulfones) were found. This result is especially valuable since, by simple changing from nitrogen- to oxygen-saturated solvent conditions, the reaction outcome can be tuned from cyclized to sulfur oxidation products. Additionally, steady-state photolysis, electrochemistry, and laser time-resolved spectroscopic studies confirmed that these reactions mainly proceeded by intramolecular electron transfer (ET) between the triplet excited saccharin moiety and sulfur atom.